Influence of stress associated with chronic alcohol exposure on drinking. (1st August 2017) - Becker, Howard C.
Abstract: Stress is commonly regarded as an important trigger for relapse and a significant factor that promotes increased motivation to drink in some individuals. However, the relationship between stress and alcohol is complex, likely changing in form during the transition from early moderated alcohol use to more heavy uncontrolled alcohol intake. A growing body of evidence indicates that prolonged excessive alcohol consumption serves as a potent stressor, producing persistent dysregulation of brain reward and stress systems beyond normal homeostatic limits. This progressive dysfunctional (allostatic) state is characterized by changes in neuroendocrine and brain stress pathways that underlie expression of withdrawal symptoms that reflect a negative affective state (dysphoria, anxiety), as well as increased motivation to self-administer alcohol. This review highlights literature supportive of this theoretical framework for alcohol addiction. In particular, evidence for stress-related neural, physiological, and behavioral changes associated with chronic alcohol exposure and withdrawal experience is presented. Additionally, this review focuses on the effects of chronic alcohol-induced changes in several pro-stress neuropeptides (corticotropin-releasing factor, dynorphin) and anti-stress neuropeptide systems (nocicepton, neuropeptide Y, oxytocin) in contributing to the stress, negative emotional, and motivational consequences of chronic alcohol exposure. Studies involving use of animal models have significantly increased our understanding of the dynamic stress-related physiological mechanisms and psychological underpinnings of alcohol addiction. This, in turn, is crucial for developing new and more effective therapeutics for treating excessive, harmful drinking, particularly stress-enhanced alcohol consumption. This article is part of the Special Issue entitled "Alcoholism". Highlights: Stress alters drinking and progression of addiction in a complex manner. Prolonged excessive alcohol consumption is a potent stressor. Chronic alcohol produces persistent dysregulation of brain reward and stress systems. Chronic alcohol engages stress and anti-stress neuropeptide systems. chronic alcohol adaptations underlie stress, negative affect, and motivational behaviors.